The management skills of academic head librarians in Quezon City - Tampoc, Leoghenes A.; Gonzales, Grace Marie B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2002)
The research paper focused on the level of management skill of the academic head librarians in Quezon City. Also, this research was concerned with the educational attainment and length of work experience of these academic head librarians. The researcher aimed to determine whether these academic head librarians have a low or high management skill and whether their educational attainment and length of work experience is related to their level of management skill.
Of the 28 academic head librarians from different schools and universities in Quezon City 27 participated in the study. The respondents were grouped according to their educational attainment and length of work experience. Descriptive Statistical Method, specifically, the averaging of scores was used to compute for the respondents' level of management skill. One Way Anova and the Paired Sample Test were used to know if there is a relationship between the academic head librarians' level of management skill and their educational attainment and length of work experience.
The findings showed that in general, the academic head librarians from different colleges and universities in Quezon City have a high level of management skill with a mean score of 4.2. Also, the findings revealed that there is a relationship between the academic head librarians' management skill and their educational attainment and length of work experience.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: Academic librarians -- Philippines -- Quezon City